Toni Morrison on mothers and motherhood (Bradford : Demeter Press, 2017)
This collection of essays explores the gamut of Toni Morrison's novels from her earliest to her most recent. Each of the essays examines the various ways in which Morrison's work delineates and interrogates Western culture's ideological norms of mothers, motherhood, and mothering. The essays consider Morrison's female, and in some cases male, characters as challenging the concept that mothering and motherhood is a stable notion. The essays reveal both that mothering is a central concept in Morrison's work and that an examination of this pervasive notion illuminates her corpus as a whole. Toni.
Part I: "Othermothering" -- Masculine othermothering in Toni Morrison's Home / Susan Neal Mayberry -- "Not a maternal drudge ... not ... an acid-tongued shrew ": The complexity of Ruth and Pilate in Toni Morrison's Song of Solomon / Jill Goad -- "You've already got what you need, sugar": Southern and maternal identity in Toni Morrison's Song of Solomon / Anna Hinton -- Part II: "Bad" mothering -- Studies in M(othering): Unpacking the "wicked thing" in Toni Morrison's A Mercy and Beloved / Veena Deo -- Rethinking, rewriting self and other in Toni Morrison's Love / Lee Baxter -- The trauma of second birth: Double consciousness, rupture, and Toni Morrison's Beloved / Lauren A. Mitchell -- "Are you sure she was your sister?" Sororal love and maternal failure in Toni Morrison's Paradise / Kristin M. Distel -- From sweetness to Toya Graham: Intersectionality and the (Im)possibilities of maternal ethics / Jesse A. Goldberg -- Racialized intimacies and alternative kinship relations: Toni Morrison's Home / Rosanne Kennedy -- Part III: Lack of mothering -- Failed mothers and the black girl-child victim of incestuous rape in The Bluest Eye and Push / Candice Pipes -- Mothering oneself in Sula / Marth Satz -- Black motherhood, beauty, and soul [murder-] wound / Althea Tait -- "They took my milk": The multiple meanings of breastmilk in Toni Morrison's Beloved / Barbara Mattar -- Brother-mother and othermothers: Healing the body of physical, psychological, and emotional trauma in Toni Morrison's Home / Tosha K. Sampson-Choma.
JSTOR
Keywords: Morrison, Toni -- Criticism and interpretation; Morrison, Toni; Motherhood in literature; Mothers in literature; Maternité dans la littérature.; Mères dans la littérature.; Motherhood; Parenting; FAMILY & RELATIONSHIPS; Women's Health; HEALTH & FITNESS; Feminism & Feminist Theory; SOCIAL SCIENCE; Women's Studies; Motherhood in literature; Mothers in literature; Electronic books; Criticism, interpretation, etc